The impact of obstructive sleep apnea on nonalcoholic fatty liver disease in patients with severe obesity. Issue 4 (16th February 2016) - Benotti, Peter; Wood, G. Craig; Argyropoulos, George; Pack, Allan; Keenan, Brendan T.; Gao, Xiang; Gerhard, Glenn; Still, Christopher
Abstract : Objective: Obstructive sleep apnea (OSA) is common among candidates for bariatric surgery. OSA and its associated intermittent hypoxia have been implicated in the pathogenesis of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis. A large cohort of bariatric surgery patients was studied in an effort to explore the relationship between OSA severity, hypoxia, metabolic syndrome, and the severity of NAFLD. Methods: Bariatric surgery candidates who underwent both polysomnography and liver biopsy were studied. The severity of OSA as determined by the apnea‐hypopnea index (AHI) and parameters of hypoxia was studied in relation to extent of abnormalities of liver histology as measured by the presence of hepatic steatosis, inflammation, and fibrosis. Results: The study cohort included 362 patients with a mean age of 46.2 years and BMI of 49.9 kg/m 2 . On the basis of AHI, 26% of the cohort had no OSA, 32% mild OSA, 22% moderate OSA, and 20% severe OSA. For the study subjects without metabolic syndrome, positive correlations were found between OSA severity, as measured by AHI, and parameters of hypoxia, with the severity of NAFLD. Conclusions: OSA severity and its accompanying hypoxia are associated with the severity of NAFLD.